“Estudio comparativo de un análisis y diseño estructural de una edificación de seis pisos ubicada en la ciudad de Riobamba usando los parámetros del ACI 318-08 considerados en la norma NEC (2015), y los parámetros del ACI 318-14.” - Bejarano Cevallos., Danny Rodrigo (2017)
Ecuador, located in a zone of high seismic risk, constantly supports earthquakes of considerable magnitudes. This forces professionals in the construction sector to carry out structural designs by applying design codes that are becoming more rigorous. In our case, the Ecuadorian Construction Standard NEC (2015) has been recently applied, which is based on the parameters of the American Concrete Institute (ACI) code 318-08. However, in the last years, the ACI 318-14 code has been more used internationally, but this code is not considered in the NEC (2105) code. In the present study, a comparison between the NEC (2015) and ACI 318-14 codes was performed, evaluating parameters and requirements for analysis and structural design of buildings. For this, a six-story reinforced concrete building for departments was studied. On the first floor, a parking lot is located, and on the upper floors, single-family apartments are located on each floor. The building consists of: a 20 cm thick lightened slab (result of a pre-dimensioning), a framed system with beams, columns and shear walls located in X and Y. This structure is not built. Therefore, to carry out this research was necessary to include the architectural design. In this research, a documentary, comparative, descriptive and scientific study was performed, taking into account that the structural design is based on the Ultimate Resistance Method. From the analysis, it was possible to determine that the cracked moments of inertia established in the ACI 318-14 code result in a more flexible behavior of the structure compared to the analysis performed using the NEC (2015) code, with an increase in internal forces and therefore an increase of reinforcing steel. The largest displacement of the structure was evidenced in the sixth floor (X direction), which is 14% greater than the displacement produced using the NEC (2015) code. Finally the design of the building was carried out considering the respective parameters and requirements for seismic design that are specified both in the NEC (2015) and ACI 318-14 codes.